Role of QRS amplitude, fractionation and duration in predicting clinical response to anti-inflammatory treatment in cardiac sarcoidosis. (14th October 2021) - Arceluz, M; Frankel, D; Tschabrunn, C; Santangeli, P; Bravo, P; Supple, G; Muser, D; Callans, D; Schaller, R; Hyman, M; Kumareswaran, R; Riley, M; et al.
Abstract: Background: Low QRS amplitude (QRSa), QRS fractionation (QRSf) and longer QRS duration (QRSd) are markers of myocardial fibrosis and inflammation in non-ischemic cardiomyopathy (NICM). Objective: To determine if reduction of inflammation with treatment of cardiac sarcoidosis (CS) may reverse these 12 lead ECG parameter changes. Methods: 21 patients (pts) with CS and VT ablation with a positive baseline positron emission tomographic (PET 1) scan were studied. All pts received prednisone ≥40 mg for 4 to 8 weeks followed by a taper and maintenance with methotrexate ± low-dose prednisone, <10 mg/day, until clinically stable and resolution of inflammation on PET 2 one year after initial. In addition, pts with low LV ejection fraction (13/21) received guideline directed medical therapy for heart failure. Pts at 1yr with positive PET2 (9) were compared to those with negative PET2 (12). Baseline and 1yr 12-lead ECGs were analyzed for QRSd, ≥2QRSf contiguous leads and QRSa in the limb leads. Results: Pts in PET2(+) vs PET2(−) groups has similar gender (men 89% vs 100%, p=0.42), age (57±8 vs 56±10 years, p=0.8) and LV ejection fraction (41±11 vs 46±11, p=0.31). Baseline 12-lead ECGs showed similar QRSd, ≥2QRSf contiguous leads and QRSa for PET2(+) vs PET2(−); P all >0.15 (Table 1). At 1 yr there was a lower prevalence of ≥2QRSf contiguous leads and strong trend for shorter QRS duration and larger QRSa in lead DI if PET2(−) vs PET2(+). 4 pts demonstrated loss of QRSf 2 contiguous leads and/or increase in QRSa in DI by at least 0.15 mV from baseline if PET2(−) and none if PET2(+). Conclusions: In pts with CS and VT, reversal of inflammation may result in a greater QRSa and reduction in QRSf. An increase in QRSa in lead 1 by >0.15mV and/or loss of QRSf identifies a clear positive response to treatment and negative PET at 1 year. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Richard T and Angela Clark Innovation Fund in Cardiovascular Medicine, the Mark S Marchlinski EP Research and Education Fund and the Winkelman Family Fund in Cardiovascular Innovation.